Onward Christian Soldiers: Lyman Abbott's Justification of the Spanish-American War - Wetzel, Benjamin J. (A journal of church and state, 2012)
In November 1897, a veritable who's who of liberal Protestants descended upon Brooklyn, New York. These men, including Washington Gladden, George A. Gordon, Wil